How long was the working day in London in the 1750s? Evidence from the courtroom - Voth, H (University of Oxford, 1996)
Little is known about the length of the working year in pre-industrial times. This paper develops a new method for analysing patterns of time-use in the past. Witnesses' accounts in court records, it will be argued, reflect the actual behaviour of a group that is representative of the population at large. This new technique is applied to London during the middle of the eighteenth century. Results are compared with evidence from other eighteenth-century sources. These findings have important implications for our understanding of the Industrial Revolution. Our estimate of the number of working days helps to resolve some apparent contradictions between wage and income measures.